Study of Rock Burst Risk Evolution in Front of Deep Longwall Panel Based on Passive Seismic Velocity Tomography. (29th November 2020) - Zhou, Kunyou; Dou, Linming; Gong, Siyuan; Li, Jiazhuo; Zhang, Jinkui; Cao, Jinrong
Abstract : Monitoring and early-warning are critical for the prevention and controlling of rock burst in deep coal mining. In this study, rock burst risk assessment criterion was built based on the correlativity between seismic velocity and stress state in coal and rock body. Passive seismic velocity tomography using mining-induced seismic waves was conducted regularly and continuously. The evolution of rock burst risk and range in front of a deep longwall panel with folds and adjoining goaf was determined. The influence of pressure-relief measures on rock burst risk was analyzed. The study results indicate that burst risk level and range during panel retreating increase first and then decrease, the peak is reached when it is located at 1# syncline shaft area. When approaching the crossheading, high burst risk zones distribute along the crossheading and further intersect with those in 1# syncline shaft area. Burst risk zones in the inclination of panel show distinct zoning features. Tomography results are in good agreement with the drilling bit result, rock burst occurrence, microseismic activity, and working resistance of hydraulic supports. Pressure-relief measures and mining layout have a distinct influence on burst risk of longwall panel. For prevention and controlling of rock burst risk in deep coal mining, pressure-relief measures should be optimized based on passive tomography results.